A Student Perspective on ELAM and its Educational Program - Razel Remen; Lillian Holloway (Social Medicine Publication Group, 2008)
The health of the world's population is divided into two groups, those who have access to health care services and those who do not. The effects of this divide can be seen on the international level where life expectancy in Switzerland averages 80 years as opposed to 38 years in Zambia. Infant mortality rates are often used as a general indicator of health and socioeconomic conditions since rates are affected by factors such as access to prenatal health care. A direct relationship has been shown between higher income and education level and lower rates of infant mortality. This may explain in part an infant mortality rate of 4.5 per 1,000 live births in Connecticut in comparison with 12.2 in the Washington, D.C. area. A major influence in access to services is the availability of trained health care workers. The World Health Organization estimates that the world will need at least 4,250,000 additional health workers to address these health disparities3. In the face of this work force crisis we are left wondering how to fill in the gaps left by the mass exodus of health workers from developing nations to industrialized ones. Cuba has tried to address these problems by sending thousands of healthcare professionals to work in some of the most impoverished and medically underserved regions in the world. Over the years, their attempts have evolved to include training professionals from underserved areas to provide enduring sources of health care for their populations. Perhaps the most valiant of efforts was the creation of the Latin American School of Medicine in Cuba (called ELAM, Escuela Latinoamericana de Medicina), which currently is training over 10,000 students from at least 27 countries, including the United States. Despite ELAM's impressive numbers, its founders recognized that solutions to what has become a global health care crisis depend not only on the number of physicians produced but also on how they are trained to be providers of care. To that end training is oriented toward primary care, public health and hands-on clinical experience. Perhaps no one can speak better about the training at ELAM than the actual students